Kajian Teknis dan Ekonomis Pemberaian Overburden dengan Metode Ripping pada Tambang Batubara PT Duta Tambang Rekayasa Kecamatan Seimenggaris, Kabupaten Nunukan, Provinsi Kalimantan Utara - Ayu Ramadhina; Zaenal; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Duta Tambang Rekayasa is a company engaged in coal mining with an IUP of 1,700 Ha. Has a Stripping Ratio (SR) of 12 BCM OB/Ton BB with a coal production target of 50,000 tons per month and an Overburden (OB) stripping target of 600,000 BCM per month. OB stripping based on Rippability in that area is included in the category of using the Ripping Method. The actual results of Ripping production are not yet known, so it is necessary to study both from a technical and economic point of view. The technical review consists of calculating the achievement of productiontargets by analyzing the production of Ripping and digging activities and the need for tools. The study from an economic perspective is the calculation of the estimated cost of the equipment. Data that needs to be analyzed is the production of Bulldozers and Backhoes, economic data in the form of equipment ownership, and operating costs. The study used three tools and observed, namely the Komatsu D375A Bulldozer, the Liebherr 756 Bulldozer, and the Hitachi 870 LCH 8G Backhoe. Based on the research results, it can be analyzed regarding the average Ripping production using the Komatsu D375A Bulldozer of 1440.74 BCM/hour/tool, with a production target of 300,000 BCM/month/tool. This tool has been (fulfilled) with a production yield of 393,782.33 BCM/month/ tools, for the estimated Ripping costs incurred Rp. 2,286.61,- BCM/hour. While the average Ripping production using the Liebherr 756 Bulldozer is 894.52 BCM/hour/tool. Production of the Liebherr 756 Bulldozer (not fulfilled) with a yield of 200,837.45 BCM/month/tool is suggested to add to 2 units of equipment, with an estimated Ripping cost of Rp. 2550.33,- BCM/hour. Hitachi ZX870LCH-5G Backhoe loading and unloading equipment production (not yet fulfilled) with a production output of 130,049.83 BCM/month/tool is suggested to add to 5 units of equipment, with an estimated digging-loading cost of Rp.3,638.32,- BCM/hour. Abstrak. PT Duta Tambang Rekayasa merupakan perusahaan yang bergerak di bidang pertambangan batubara dengan IUP seluas 1.700 Ha. Memiliki StRipping Ratio (SR) 12 BCM OB/Ton BB dengan target produksi batubara sebesar 50.000 ton per bulan dan target pengupasan Overburden (OB) sebesar 600.000 BCM per bulan. Pengupasan OB berdasarkan Kemampugaruan (Rippability) pada daerah tersebut termasuk kategori menggunakan Metode Ripping. Belum diketahui secara aktual hasil produksi Ripping maka perlu dilakukan kajian baik dari segi teknis dan ekonomis. Kajian teknis terdiri dari perhitungan pencapaian target produksi dengan analisis produksi aktivitas Ripping dan aktivitas gali-muat dan kebutuhan alat. Kajian dari segi ekonomis yaitu perhitungan estimasi biaya alat. Data yang perlu di analisis berupa produksi Bulldozer dan Backhoe, data ekonomi berupa biaya kepemilikan dan biaya operasi alat. Penelitian menggunakan tiga alat dan yang diamati, yaitu Bulldozer Komatsu D375A, Bulldozer Liebherr 756 dan Backhoe Hitachi 870 LCH 8G. Berdasarkan hasil penelitian dapat dianalisis mengenai produksi rata-rata Ripping menggunakan Bulldozer Komatsu D375A sebanyak 1440,74 BCM/jam/alat, dengan target produksi 300.000 BCM/bulan/alat alat ini sudah (terpenuhi) dengan hasil produksi 393.782,33 BCM/bulan/alat, untuk estimasi biaya Ripping yang dikeluarkan sebesar Rp. 2.286,61,- BCM/jam. Sementara produksi rata-rata Ripping menggunakan Bulldozer Liebherr 756 sebanyak 894,52 BCM/jam/alat. Produksi Bulldozer Liebherr 756 (belum terpenuhi) dengan hasil 200.837,45 BCM/bulan/alat disarankan menambah menjadi 2 unit alat, dengan estimasi biaya Ripping yang dikeluarkan sebesar Rp. 2.550,33,- BCM/jam. Hasil produksi alat gali-muat Backhoe Hitachi ZX870LCH-5G (belum terpenuhi) dengan hasil produksi 130.049,83 BCM/bulan/alat disarankan menambah menjadi 5 unit alat, dengan estimasi biaya gali-muat sebesar Rp.3.638,32,- BCM/jam.